A commentary on Catullus 64, lines 1-201 - Trimble, GC (2010)
The thesis consists of detailed commentary on the first 201 lines of Catullus 64, together with an edited text and apparatus criticus. It represents about half a planned commentary on the whole poem, which will also include an introduction. The commentary begins by discussing the poem’s Argonautic opening, its use of allusion to negotiate generic relationships with epic and tragedy, and its exploration of narrative, pictorial and first-person ‘lyric’ modes. As the narrative jumps to Peleus’ wedding, the commentary examines the complicated moral signals about Roman luxury and the golden age sent by the description of the gleaming palace surrounded by abandoned fields. The transition to the description of Ariadne prompts an examination of how this ‘disobedient’ ecphrasis emphasises details that a picture could not literally convey, together with an analysis of the male narrator’s objectifying presentation of a woman in distress. The ecphrasis proper is then disrupted by a ‘flashback’ covering Ariadne’s first encounter with Theseus and his fight with the Minotaur: the commentary explores the ways in which shifting focalisation complicates the reader’s judgement of Theseus’ heroism. Finally, the thesis looks at Ariadne’s speech as an intertextual node, investigating the meanings generated by its relationships with other speeches from both earlier and later in Greek and Roman poetic traditions, and examining how each theme or topos is used in this particular situation both by the alluding poet and by Ariadne herself. More discursive notes introducing the various sections are interspersed with shorter lemmata considering textual, metrical, linguistic and cultural-historical issues as well as literary interpretation. The commentary aims both to open up the possibilities of meaning offered by individual words and phrases, and to advance critical understanding of key aspects of the whole poem, such as its narratorial voice, engagement with visuality and place in literary history.